Fusarium head blight monitoring in wheat ears using machine learning and multimodal data from asymptomatic to symptomatic periods - Mustafa, Ghulam; Zheng, Hengbiao; Li, Wei; Yin, Yuming; Wang, Yongqing; Zhou, Meng; Liu, Peng; Bilal, Muhammad; Jia, Haiyan; Li, Guoqiang; Cheng, Tao; Tian, Yongchao; et al. (Frontiers in Plant Science, 2023)
The growth of the fusarium head blight (FHB) pathogen at the grain formation stage is a deadly threat to wheat production through disruption of the photosynthetic processes of wheat spikes. Real-time nondestructive and frequent proxy detection approaches are necessary to control pathogen propagation and targeted fungicide application. Therefore, this study examined the chlorophyll-related phenotypes or features from spectral and chlorophyll fluorescence for FHB monitoring. A methodology is developed using features extracted from hyperspectral reflectance (HR), chlorophyll fluorescence imaging (CFI), and high-throughput phenotyping (HTP) for asymptomatic to symptomatic disease detection from two consecutive years of experiments. The disease-sensitive features were selected using the Boruta feature-selection algorithm, and subjected to machine learning-sequential floating forward selection (ML-SFFS) for optimum feature combination. The results demonstrated that the biochemical parameters, HR, CFI, and HTP showed consistent alterations during the spike–pathogen interaction. Among the selected disease sensitive features, reciprocal reflectance (RR=1/700) demonstrated the highest coefficient of determination (R2) of 0.81, with root mean square error (RMSE) of 11.1. A combination of two to three kinds of features was found optimum for asymptomatic disease detection using ML-SFFS with an average classification accuracy of 87.04% that gradually improved to 95% for a DS level of 20%. However, multivariate k-nearest neighbor model outperformed the competing multivariate and univariate models with an accuracy of R2 = 0.92 and RMSE = 10.21. The study demonstrated the fusion of chlorophyll-related phenotypes with the ML-SFFS might be a good choice for crop disease detection.